2023
DOI: 10.1021/acsapm.3c02150
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Antifouling Surface Polymer Brushes

Xin Xu,
Yixin Chang,
Yutong Gong
et al.

Abstract: Biofouling caused by nonspecific adsorption of biomolecules and organisms such as proteins, cells, and bacteria to material surfaces is a significant challenge for numerous important applications. An effective approach to addressing this problem is to coat antifouling polymers on the material surfaces to impart the demanded antifouling properties and repel nonspecific biological adhesion. In this review, we summarized recent advances in surface antifouling polymer brushes which have emerged in the past decade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 348 publications
(603 reference statements)
0
1
0
Order By: Relevance
“…Slippery liquid-infused porous surfaces (SLIPS) and superhydrophobic surfaces may resist nonspecific adherence, , but their employment is constrained due to their inability to function in complex settings. , Nonspecific adhesion can also be resisted by surface hydrophilic polymer brushes, and zwitterionic polymer brush materials have been widely recognized for their excellent antifouling properties. It has been shown that these hydrophilic polymers can attract water molecules through hydrogen bonding or electrostatic interaction to form a hydrated layer . Since the water molecules in this hydrated layer can tolerate high pressures, they can serve as a solid physical and energy barrier that prevents the adsorption of proteins. ,, Spectroscopic methods, including nuclear magnetic resonance (NMR) spectroscopy, X-ray diffraction (XRD), infrared (IR) spectroscopy, and atomic force microscopy (AFM), have been employed to investigate the antifouling properties of polymer brushes and the structure of the interfacial water. Despite notable advancements, the field faces ongoing challenges in quantifying the interactions among polymer brushes, water molecules, and proteins. Moreover, uncovering the correlation between the material and structure of polymer brushes and their antifouling properties remains a significant hurdle.…”
Section: Introductionmentioning
confidence: 99%
“…Slippery liquid-infused porous surfaces (SLIPS) and superhydrophobic surfaces may resist nonspecific adherence, , but their employment is constrained due to their inability to function in complex settings. , Nonspecific adhesion can also be resisted by surface hydrophilic polymer brushes, and zwitterionic polymer brush materials have been widely recognized for their excellent antifouling properties. It has been shown that these hydrophilic polymers can attract water molecules through hydrogen bonding or electrostatic interaction to form a hydrated layer . Since the water molecules in this hydrated layer can tolerate high pressures, they can serve as a solid physical and energy barrier that prevents the adsorption of proteins. ,, Spectroscopic methods, including nuclear magnetic resonance (NMR) spectroscopy, X-ray diffraction (XRD), infrared (IR) spectroscopy, and atomic force microscopy (AFM), have been employed to investigate the antifouling properties of polymer brushes and the structure of the interfacial water. Despite notable advancements, the field faces ongoing challenges in quantifying the interactions among polymer brushes, water molecules, and proteins. Moreover, uncovering the correlation between the material and structure of polymer brushes and their antifouling properties remains a significant hurdle.…”
Section: Introductionmentioning
confidence: 99%